Circuit Breaker with Recloser - Al-Jamal, Nadeen; Hamdan, Tawfeeq; Khader, Basel; Albaz, Ahmad (My University, 2019)
as well-known power system protection is very essential for modern power system to make the system is reliable even the faults occur from time to time. There are different protective devices used in the power system each device operates in a different manner. In this project a smart circuit breaker is proposed by using Arduino, the main function for the proposed breaker combines both recloser and distance relay together. The protection scheme of the recloser will be used to detect when the fault occurs and recloses when the fault is cleared. The distance relay will identify the distance of the faults for long transmission power lines.